Quantitative, chemically specific imaging of selenium transformation in plants - Pickering, Ingrid J. (The National Academy of Sciences, 2000)
Quantitative, chemically specific images of biological systems would be invaluable in unraveling the bioinorganic chemistry of biological tissues. Here we report the spatial distribution and chemical forms of selenium in Astragalus bisulcatus (two-grooved poison or milk vetch), a plant capable of accumulating up to 0.65% of its shoot dry biomass as Se in its natural habitat. By selectively tuning incident x-ray energies close to the Se K-absorption edge, we have collected quantitative, 100-μm-resolution images of the spatial distribution, concentration, and chemical form of Se in intact root and shoot tissues. To our knowledge, this is the first report of quantitative concentration-imaging of specific chemical forms. Plants exposed to 5 μM selenate for 28 days contained predominantly selenate in the mature leaf tissue at a concentration of 0.3–0.6 mM, whereas the young leaves and the roots contained organoselenium almost exclusively, indicating that the ability to biotransform selenate is either inducible or developmentally specific. While the concentration of organoselenium in the majority of the root tissue was much lower than that of the youngest leaves (0.2–0.3 compared with 3–4 mM), isolated areas on the extremities of the roots contained concentrations of organoselenium an order of magnitude greater than the rest of the root. These imaging results were corroborated by spatially resolved x-ray absorption near-edge spectra collected from selected 100 × 100 μm(2) regions of the same tissues.